Factors influencing perceived stress in pregnant women during cyclones in Queensland, Australia - Cynthia Parayiwa; Robert Clark; David Harley; Aparna Lal; Alison Behie (Current Research in Ecological and Social Psychology, 2023)
Objectives: During natural disasters, pregnant women are at risk of experiencing stress related pregnancy complications. This study explores factors influencing perceived stress reported by 90 women surveyed about their pregnancy during cyclones in Queensland, Australia. Methods: Perceived stress was measured using the 10 item Perceived Stress Scale and objective hardship using the Traumatic Stress Schedule. Maternal characteristics were captured using validated questions pilot tested for reliability and validity. Hierarchical linear regression was used to test factors across three analysis blocks (maternal sociodemographic characteristics, mediating factors, and objective hardship). The effect of factor interactions was tested both within and between analysis blocks. Results: Separate factors were found to have no significant effect on perceived stress. However, a significant moderating effect was found between maternal country of birth and experiences of objective hardship. Perceived stress levels were higher for mothers born in New Zealand who also experienced cyclone stressors (β = 0.48, p = 0.014), and mothers born in the United Kingdom/Western Europe who experienced non-cyclone stressors (β = 0.44, p = 0.014) and pregnancy complications (β = 0.43, p = 0.011). Conclusion: Recall and sampling bias may influence perceived stress reported. However, mothers migrating to a different country are at a higher risk of experiencing disaster stressors. This can be due to limited social networks and access to resources. Identifying additional vulnerabilities within an existing disaster priority group supports informed risk mitigation.